The Existence of The Art of Jaran Bodhag in Probolinggo During 2004-2017 - Harits Al Ayyubih; Sugiyanto Sugiyanto; Bambang Soepeno (History Education, University of Jember, 2020)
The art of Jaran Bodhag is an interesting traditional art and has it’s own uniquenesscompared to the other form of the art of Jaranan. Jaran Bodhag is the result of the inovationof people in Probolinggo, because they can’t perfom Jaran Kencak. This art became theicon of Probolinggo that shows the Pandhalungan culture of Probolinggo. The problems inthis research are: What is the reason behind the creation of Jaran Bodhag?; How is theexistence of the art of Jaran Bodhag during 2004-2017 in Probolinggo? ; What is the artist,people, and the government of Probolingo effort to preserve the existence of the art ofJaran Bodhag in Probolinggo? The purpose of this research is to describe the existence ofthe art of Jaran Bodhag during 2004-2017. The research method that being used is hitoricalresearch method with the cultural anthropology approach and functionalism theory. Thisresearch is expected to give a contribution and information about the connection ofPendhalungan culture and the existence of Jaran Bodhag. The conclusion of this research isthe the reason behind the creation of Jaran Bodhag and it’s existential form during 20042017,and the artist, people, and the government of Probolingo effort to preserve theexistence of the art of Jaran Bodhag.